Improved Performance of an Epoxy Matrix as a Result of Combining Graphene Oxide and Reduced Graphene - L. Ramos-Galicia; L. N. Mendez; Ana Laura Martínez-Hernández; A. Espindola-Gonzalez; I. R. Galindo-Esquivel; R. Fuentes-Ramirez; C. Velasco-Santos (International Journal of Polymer Science)
We present an easy and effective way to improve the mechanical properties of an epoxy matrix by reinforcing it with a combination of graphene oxide (GO) and reduced graphene oxide (RGO). These nanocomposites were prepared with different load of nanofillers: 0.1, 0.4, 0.7, 1.0 wt% and a neat epoxy. Ratios of graphene oxide and reduced graphene (GO : RGO) employed were: 0 : 1, 0.25 : 0.75, 0.5 : 0.5, 0.75 : 0.25, and 1 : 0. Results show that with only 0.4 wt% and a ratio 0.2 : 0.75 of GO : RGO, tensile strength and tensile toughness are 52% and 152% higher than neat epoxy while modulus of elasticity was improved ~20%. The obtained results suggest that it is possible achieve advantageous properties by combining graphene in oxidized and reduced conditions as it shows a synergic effect by the presence of both nanofillers.